Acondicionamiento físico pre-operatorio en pacientes adultos con cáncer colorrectal. - Albán Naranjo, Alisson Estefanía (2024)
In the present scenario, the application of rehabilitation in the context of cancer is a relatively novel field, which is a process aimed at identifying deficiencies and providing specific exercises to mitigate both the incidence and severity of such shortcomings before initiating treatment. This prehabilitation approach is characterized by its multimodal approach, which extends from nutritional care to physical and psychological training of the patient, consistent with the relevance of our area of research. The purpose of this degree work lies in analyzing the effects of preoperative physical conditioning in adult patients diagnosed with colorectal cancer and undergoing elective surgery through a specialized literature review. For this purpose, an exhaustive retrospective qualitative documentary search of a descriptive nature has been carried out using the inductive research method. In addition, many digital scientific databases were used, such as PubMed, WILEY, BMC, Cochrane, Scielo, ScienceDirect, Google Scholar, and Pedro. Subsequently, the selected articles have been meticulously evaluated using the Prisma, PEDro, and Newcastle-Ottawa (NOS) methodological scales, respectively, including 32 scientific studies that meet the rigorous quality criteria established. The results obtained through the analysis of these studies have revealed variations in the statistical significance observed in the comparison between the intervention and control groups in the different clinical trials. Nevertheless, in general terms, it has been found that preoperative physical conditioning has a positive effect on patients with colorectal cancer undergoing elective surgery, which is reflected in relevant aspects such as postoperative complications, length of hospital stays, functional capacity, muscle strength, and body composition.